Perbedaan Status Sosial Di Tengah Masyarakat: Studi Kasus Tradisi Alek Bajawek Di Kabupaten Dharmasraya 1960-2005 - Nurfalina, Yuliana; Nengsih, Fitria; Alhuzaini, Muhammad; Darmawan, Budi; Anggraini, Riri (Universitas Semarang, 2023)
As a tradition that has long existed in the lives of the people of Dharmasraya Regency, the Alek Bajawek Tradition is always held only on certain days. This research aims to reveal the Alek Bajawek Tradition in Kenagarian Koto Baru Dharmasraya. In contrast to the implementation of other traditions which involve all people in every procession, the Alek Bajawek tradition can only be carried out by certain people, such as Urang Nan Ampek Jinih. The research method used in this writing is the historical research method, with data collection carried out directly in the field through interviews and observation as primary sources. Meanwhile, researchers obtain secondary sources through the library. Then in the historical method there are several stages that must be carried out, such as heuristics, source criticism, analysis and writing. The results of this research explain the beginning of the emergence of the Alek Bajawek tradition at the same time as the Koto Besar Kingdom in Koto Baru Dharmasraya District, the existence of the Alek Bajawek tradition as a special tradition in the form of respect from the community for Urang Nan Ampek Jinih and is usually called Alek Gadang or Alek Rajo . However, this phenomenon indirectly makes a difference in the social status between a king or other leading figure and ordinary people.